تحليل ونمذجة العوامل المؤثرة على حدوث المطرقة المائية في محطات ضّخ مياه الري التابعة لمشروع ري هضبة عين البيضاء - سامي قدسية; علا الغدا (Tishreen University, 2017)
يقوم البحث بدراسة آليات حدوث مشكلة المطرقة المائية التي قد تسبب تدميراً لشبكات أنابيب الري ومحطات الضخ وتجهيزاتها, التابعة لمشروع ري ناحية عين البيضاء وجوارها في شمال شرق مدينة اللاذقية, حيث يسعى المشروع إلى إرواء 5000 هكتار من الأراضي بمياه يتم جرها من بحيرة سد 16 تشرين . ويتكون المشروع من أربعة محطات ضخ بالإضافة إلى شبكات ري رئيسية و فرعية. استُخدمت في هذه المحطّات أنابيب مصنوعة من الفولاذ (Steel). كما أن الخزّان الرّئيسي للمشروع هو خزّان قسمين. تمّ في هذا البحث بمساعدة برنامج الشبكات المضغوطة Water CADوبرنامج Water Hammerبتحديد الضغوط الأعظمية والسرعات في حالتي الجريان المستقر وغير المستقر، وتحديد الضغوط الأعظمية في حالة الجريان غير المستقر من خلال وضع آلية لحدوث مطرقة مائية ناجمة عن الإغلاق المفاجئ لصمام التحكم, فنتجت قيم ضغوط عالية أكبر من قدرة تحمل الأنابيب والتجهيزات لها, بالإضافة إلى وضع آلية آخرى يبين تأثير عدم استخدام صمام عدم الرجوع في حدوث المطرقة المائية ودوره كوسيلة حماية جيدة منها, فنتجت قيم ضغوط عالية وخطيرة أكبر بكثير من قدرة تحمل الأنابيب والتجهيزات. كذلك استخدمنا خزان هواء مضغوط في آلية ثالث كوسيلة حماية جيدة من المطرقة المائية فوجدنا من خلال قيم الضغوط الأعظمية الناتجة أن خزان الهواء المضغوط وسيلة الحماية الأفضل؛ حيث منع أي زيادة في قيم الضغوط الأعظمية عند حدوث المطرقة المائية وحافظ على قيمها التي كانت في حالة الجريان المستقر. The research study scenarios water hammer problem that may cause the destruction of the irrigation pipes, pumping stations and equipmen and part of the irrigation project in terms Ain Beida and its environs in the north-eastern city of Latakia, where the project seeks to quench 5,000 hectares of land with water pumped from Lake Dam November 16 occurrence . It consists of four pumping stations in addition to major irrigation systems and irrigation systems subsidiary. Used in these stations pipes made of steel (Steel) , The reservoir project's main reservoir is two. Bently and Water CAD V8 XM Edition we have in this research with the help of the CD-networking program Modeling of these stations to save time and effort in the study, are HAMMER V8 XM Edition Determine Adhamiya pressures and velocities in the case of runoff stable, identifying pressures Adhamiya in the case of the flow is stable through the development scenario of a water hammer caused by the sudden closure of the valve irreversibility thus leading larger than the carrying capacity of pipes and fittings have a high pressure values, and put another scenario shows the effect of non-use non-return valve in the water hammer occurs, and its role as a good protection of them Thus leading to high pressures and dangerous far greater than the carrying capacity of the pipe fittings values, and also used the compressed air reservoir in the third scenario means other protection from water hammer, and we found through Adhamiya pressures resulting values that the compressed air tank means better protection; it has to prevent any increase in pressure values Adhamiya when water hammer occurs, and kept her on the values that were in the case of steady flow.